SURVIVAL October-November 2025. (ROUTLEDGE, 2025)
Survival, the IISS's bimonthly journal, challenges conventional wisdom and brings fresh, often controversial, perspectives on strategic issues of the moment.In this issue: Barry R. Posen maintains that European defence planners must extract maximum combat power from existing European force structures by way of a large force that can be dispatched quickly for maximum effect on Russian decision-making In the wake of the 12-Day War, Michael Eisenstadt argues that the key question is whether Israel and the United States can negotiate a broader and better nuclear deal with Iran and deter it from rebuilding its nuclear programme Nigel Gould-Davies reflects that international relations is in practice a craft rather than a science, in which individual choices and personal diplomacy are now more relevant than ever Marcel Berni and Marco Jorio assess the contradictions of Switzerland's commitment to neutrality, and how the country might embrace a less rigid version for the contemporary security environment And nine other thought-provoking pieces, as well as our regular Book Reviews and Noteworthy column.To read free articles from the journal, please visit its homepage at https://www.tandfonline.com/journals/tsur20.Editor: Dr Dana AllinManaging Editor: Jonathan StevensonAssociate Editor: Carolyn WestEditorial Assistant: Anna Gallagher